Formalization of informally acquired competences as part of academic certificate programs in healthcare - "prototype" of a model / Formalisierung informell erworbener Kompetenzen im Rahmen akademischer Zertifikatsprogramme im Gesundheitsbereich - "Prototyp" eines Modells - Wolf Alexander Karsten; Thiele Heike; Haar Markus; Kortekamp Stefanie; Braun von Reinersdorff Andrea (Sciendo, 2016)
The health care sector is facing many aspects of transformation. One aspect amongst others herein is an alteration of qualification profiles. Universities have to focus on both aspects determining future qualification profiles and increasing permeability between educational systems in a sense of optimally intermeshing competences that have been acquired at universities and those that have been acquired outside of them. This leads to the question how to create university certificate programs that offers two aspects: academic qualification on the one hand and on the other hand a possibility to identify, evaluate and certify non-formally and informally acquired competences of participating students. The ultimate goal is to identify and evaluate a person´s overall competence in a clearly defined thematic context, whereat competences that have been acquired outside universities will play an important role. Competences that have been certified by these academic programs may be used later for crediting purposes. In this report an initial prototype is being presented. It defines itself mainly as additional novel way of discussing crediting concepts.